Are primary health centers prepared for noncommunicable disease management? A facility-based mapping of gaps in coastal Karnataka, India - Utsav Raj; Kibballi Madhukeshwar Akshaya; Madhavi Bhargava (Wolters Kluwer Medknow Publications, 2021)
Background: India is in the middle of epidemiological and demographic transitions, with an estimated 63% of the deaths attributed to noncommunicable diseases (NCDs). Primary health centers (PHCs) can deliver a package of services to prevent and control NCDs. Objective: The aim of this sudy is to assess the status of health promotion activities and availability of resources for screening and the treatment of NCDs in PHCs of Dakshina Kannada district, Karnataka. Materials and Methods: A cross-sectional facility-based assessment of all the 65 functioning PHCs (2016-2017) was conducted for the status of health promotion activities, and availability of resources using a checklist evolved from the World Health Organization Package of Essential NCD Interventions framework and Indian Public Health Standards. Results: Forty-eight (74%) PHCs had displayed materials on the intake of healthy foods and avoiding junk food. Warning signs of cancer were displayed at 43 (66%) PHCs. The availability of drugs for the management of hypertension (Atenolol and Amlodepine) and diabetes mellitus (Metformin) were seen in all the PHCs. Insulin was available in 64 (98%) PHCs. Sorbitrate and Nifedefine were found in 11 (17%) and 7 (11%) PHCs. More than a quarter of the PHCs were not having the medical officer and other health-care professionals to manage NCDs. Conclusions: Preparedness of the PHCs in the health promotion domain was good. The availability of human resources, laboratory support and emergency drugs for the management of NCDs needs improvement.